Netaji Subbash Chandra Bose and the Japanese Support for National Independence Movement in India and Southeast Asia - Nguyen Manh Cuong, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
In the 20th century, the national liberation movement against imperialism and colonialism became a world-wide movement in many colonial countries (Smith 2010:9, 25–30). Each country-nation has mirrored in one way or another depending on historical and socio-political conditions, especially the leaders' way (Finlayson 2014). Under British colonial rule, the nationalist movement in India was run under the leadership of patriotic and nationalistic leaders such as “a great soul” Mahatma Gandhi (McGregor 1993:799), Rash Behari Bose, Jawaharhlal Nehru, and “a respected leader” Netaji Subhas Chandra Bose (Gordon 1990:459–460). Among them, Netaji Subhas Chandra Bose has emerged as great leader. The paper consists of an introduction, three sections and conclusion: i. Vietnam and India both looked towards Japan in the early 20th century; ii. The support of the Japanese military to INA in struggle for national independence in India and Southeast Asia, and iii. Rethinking about the contributions of Netaji Subhas Chandra Bose to India. The author tries to acknowledge the role of the military leader Netaji Subhas Chandra and his way of armed struggle through the Japanese military's support to INA in struggle for national independence in India and Southeast Asia.Received 15thDecember 2020; Revised 2nd March 2021; Accepted 20th March 2021